2023
DOI: 10.1126/science.adf2472
|View full text |Cite
|
Sign up to set email alerts
|

Fear of large carnivores amplifies human-caused mortality for mesopredators

Abstract: The challenge that large carnivores face in coexisting with humans calls into question their ability to carry out critical ecosystem functions such as mesopredator suppression outside protected areas. In this study, we examined the movements and fates of mesopredators and large carnivores across rural landscapes characterized by substantial human influences. Mesopredators shifted their movements toward areas with twofold-greater human influence in regions occupied by large carnivores, indicating that they perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
(53 reference statements)
0
6
1
Order By: Relevance
“…On the other hand, we did detect a strong, positive effect of human footprint on fox spatial activity (similar to Hradsky et al 2017a). We found no evidence human activity impacted cats -subordinate predators may prefer to avoid dominant (animal) predators over humans, even when this decision leads to higher mortality rates (Prugh et al 2023).…”
Section: Discussioncontrasting
confidence: 55%
“…On the other hand, we did detect a strong, positive effect of human footprint on fox spatial activity (similar to Hradsky et al 2017a). We found no evidence human activity impacted cats -subordinate predators may prefer to avoid dominant (animal) predators over humans, even when this decision leads to higher mortality rates (Prugh et al 2023).…”
Section: Discussioncontrasting
confidence: 55%
“…Our findings build on prior research showing that ungulates use temporally dependent habitat selection to manage risk from multiple nonhuman predators (Kohl et al, 2018, 2019) by incorporating humans into the dynamic landscape of fear. By accounting for differences in habitat use between day and night, our results suggest that humans can function as super predators (Darimont et al, 2015) while also shielding elk against predation (Berger, 2007; Prugh et al, 2023). Although the elk population was increasing in this system (Ganz, 2022), the consequences of humans simultaneously acting as a shield and super predator have the potential to be detrimental and may be important to consider for conservation (Prugh et al, 2023).…”
Section: Discussionmentioning
confidence: 91%
“…Differences in predator distribution may have ultimately reflected human activities. Bassing (2022) and Prugh et al (2023) found that wolves consistently avoided anthropogenic activities in this system regardless of the indices considered (i.e., roads, human landscape modification) or scale of analysis. In contrast, cougar avoidance of humans depended on the index considered and scale of analysis, suggesting that cougars are somewhat more tolerant of anthropogenic activities (c.f., Bassing, 2022), perhaps due to strong nocturnality.…”
Section: Discussionmentioning
confidence: 95%
“…Human impacts on carnivores manifest as a complex interplay of threats and benefits, thus making it challenging to assess their community-wide effects. Meso-carnivores are drawn to human-inhabited areas due to food subsidies (Ramesh & Downs, 2014; Srivathsa et al, 2020); this proximity often results in increased mortality and reduced fitness (Prugh et al, 2023). Roads, while providing scavenging opportunities from vehicle-caused mortalities, also heighten collision risks to the carnivores themselves (Cook & Blumstein, 2013; Planillo et al, 2018).…”
Section: Discussionmentioning
confidence: 99%